Tests for epistasis of bimD with UV repair genes representing four epistatic groups and their putative types of DNA repair in Aspergillus nidulans - Etta Kafer (Fungal Genetics Reports, 2001)
bimD6, a ts mitotic mutant sensitive to UV only in dividing cells and defective in recombination, was tested for epistasis with members of the four Uvs groups of A. nidulans. UV survival of quiescent and germinating conidia was compared. While details varied between tests, results from UV-treated germinating conidia consistently showed additive or synergistic interaction. This suggested a new type of function for bimD and perhaps indirect effects on DNA repair and recombination, in line with recent evidence for defects in chromosome cohesion and compaction in mutants of bimD and its homologs (van Heemst et al. 2001 PNAS 98:6267-6272).